(3JfejI GdegGQGJ (B:s (3GdGTQGajI h GdbjGOjI (B/s - (3GdYdGb, HTjQs ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2009)
(3egGQGJ GdJNWjW h CSGdjH GJNGP GdbQGQGJ GdaYGdI, CgejI GdJNWjW h ebheGJg , CHQR CfhGY GdNWW GdJj jYJeOgG GdeTQahf dJMbjb CgOGa efXeGJge , egGQGJ GdJhLjg h GQcGfg GdeJeKdI HGdGJUGd h GdbjGOI h GdMaR , GdQbGHI ef MjK Gdeaghe h GdBdjGJ , CSGdjH JfejI GdegGQGJ GdGOGjI h GdSdhcjI , eY JhajQ OQGSGJ MGdI h JeGQjf eJYOOI(B.s
(3eQGLY U(B.263s
Keywords: (3EJNGP GdbQGQGJ(B- (3GdEOGQIs; (3GdEHOGYs; (3GdJNWjWs; (3GdbjGOIs